2022
DOI: 10.21037/atm-22-3849
|View full text |Cite
|
Sign up to set email alerts
|

METTL7B serves as a prognostic biomarker and promotes metastasis of lung adenocarcinoma cells

Abstract: Background To research the correlation between the prognosis of patients suffering from lung adenocarcinoma (LUAD) and methyltransferase like 7B (METTL7B) expression. Methods The Cancer Genome Atlas (TCGA) database was utilized to verify METTL7B expression, and The Human Protein Atlas database was utilized to verify METTL7B expression at the tissue level. The relationship between METTL7B and LUAD prognostic data was then analyzed using the KM-plotter database. The corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
(27 reference statements)
2
7
0
Order By: Relevance
“…Several studies investigating TMT1B’s effects have highlighted a role in the regulation of cell proliferation in cancer cells. Following the loss of TMT1B expression in thyroid cancer cells, a significant decrease in proliferation was found, similar to effects seen in non-small cell lung cancer, clear cell renal cancer, and glioma cells ( 4 , 21 23 , 26 29 , 32 , 33 , 50 ). Conversely, overexpression of TMT1B in thyroid cancer and lung adenocarcinoma cells significantly promoted cell proliferation ( 29 , 50 ).…”
Section: Functional Role Of Tmt1b In Cancersupporting
confidence: 67%
See 2 more Smart Citations
“…Several studies investigating TMT1B’s effects have highlighted a role in the regulation of cell proliferation in cancer cells. Following the loss of TMT1B expression in thyroid cancer cells, a significant decrease in proliferation was found, similar to effects seen in non-small cell lung cancer, clear cell renal cancer, and glioma cells ( 4 , 21 23 , 26 29 , 32 , 33 , 50 ). Conversely, overexpression of TMT1B in thyroid cancer and lung adenocarcinoma cells significantly promoted cell proliferation ( 29 , 50 ).…”
Section: Functional Role Of Tmt1b In Cancersupporting
confidence: 67%
“…Later functional studies with purified proteins confirmed that TMT1B’s methyltransferase activity is SAM-dependent ( 13 , 16 , 17 ), while microscopy studies with cultured cells refined its subcellular localisation to the perinuclear face of the ER ( 13 , 17 , 18 ), and the surface of lipid droplets (LD) ( 18 , 19 ), rather than the Golgi body ( 18 , 20 ). Differential expression of TMT1B has been found to occur within several cancer types ( 4 ), including gliomas ( 21 25 ), non-small cell lung cancer ( 16 , 23 , 26 29 ), and acute myeloid leukemia ( 30 , 31 ). TMT1B has been proposed as a biomarker for many of these cancers since its increased transcription and protein abundance is frequently correlated with an advanced TNM (Tumour, Node, Metastasis) stage of tumour development and poor patient overall survival ( 21 27 , 29 , 31 36 ), risk of recurrence ( 35 ) and drug resistance ( 16 , 37 ).…”
Section: Introduction: Methyltransferases and The Mettl Familymentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al. have reported that METTL7B is a biomarker for prognosis and promotes the metastasis of lung adenocarcinoma cells ( 41 ). Moreover, METTL7B is mainly involved in regulating immunity and ROS generation, which are two important biological processes in both HF and lung cancer ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of METTL7B as a potential therapeutic target can improve the efficacy of EGFR inhibitors. METTL7B expression is also significantly higher in LUAD cancer tissues than in the paracancer tissues and is mainly distributed in the cytoplasm, significantly promoting LUAD metastasis [ 265 ]. RhoBTB1 and 2, members of the Rho GTPase family, regulating the expression of methyltransferases METTL7B and METTL7A, respectively; however, RhoBTB1 and 2 are often silent or mutate in a wide range of epithelial cell cancers, resulting in Golgi fragmentation-induced breast cancer cell invasion [ 266 ].…”
Section: Mettls In Tumor Chemotherapymentioning
confidence: 99%